Analisis Pembelajaran Interaktif Berbasis Diferensiasi terhadap Keaktifan dan Minat Belajar Siswa pada Pelajaran PPKn Kelas X SMA - Fatri Saleh; Hafsah Hafsah; Baiq Hapipah; Yuni Yuni; Serly Wahyuni; Suryati Suryati (Universitas Muhammadiyah Mataram, 2026)
This study aims to determine the effectiveness of the implementation of differentiation-based interactive learning in increasing the activeness and interest in learning of students in the subject of Civics (PPKn) in grade X of high school. The study used the Classroom Action Research (CAR) method which was implemented in two cycles, including the planning stage, action implementation, observation, and reflection. The research subjects were 36 grade X high school students. Data were collected through observation, interviews, questionnaires, and documentation, then analyzed descriptively qualitatively and quantitatively using percentages. The results showed that student learning activeness increased from 52.4% in the pre-cycle to 87.5% in cycle II, while learning interest increased from 58.1% to 86.2%. These findings indicate that differentiation-based interactive learning is effective in creating an active, communicative, and student-centered learning atmosphere so that it can be an alternative PPKn learning strategy to increase student participation and interest in learning.